Nanoporous Carbons from Hydrothermally Treated Alga: Role in Batch and Continuous Capacitive Deionization (CDI) - Dipendu Saha; Ryan Schlosser; Lindsay Lapointe; Marisa L. Comroe; John Samohod; Elijah Whiting; David S. Young (Molecules)
This study presents a sustainable approach for synthesizing high-performance activated carbon from Spirulina Alga through hydrothermal carbonization followed by chemical activation using potassium hydroxide. The resulting activated carbon exhibited a high Brunauer–Emmett–Teller (BET) surface area of 1747 m2/g and a total pore volume of 1.147 cm3/g, with micropore volume accounting for 0.4 cm3/g. Characterization using Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDS), X-ray Photoelectron Spectroscopy (XPS), and gas adsorption analyses confirmed the presence of hierarchical micro- and mesoporosity as well as favorable surface functional groups. The synthesized carbon was used to fabricate electrodes for membrane capacitive deionization (MCDI) along with cation and anion-selective membranes, which were then tested with saline water (500–5000 ppm) and synthetic hard water (898 ppm of total salts). The salt adsorption capacity (SAC) reached 25 (batch) to 40 (continuous) mg/g, while rapid adsorption rates with average salt adsorption rates (ASARs) values exceeding 10 (batch) to 30 (continuous) mg·g−1·min−1 during early stages were obtained. Batch MCDI experiments demonstrated a higher SAC compared to continuous operation, with non-monotonic trends in SAC observed as a function of feed concentration. Ion adsorption kinetics were influenced by ion valency, membrane selectivity, and pore structure. The specific energy consumption (SEC) was calculated as 8–21 kJ/mol for batch and 0.1–0.5 kJ/mol for continuous process. These performance metrics are on par with or surpass those reported in the recent literature for similar single-electrode CDI configurations. The results demonstrate the viability of using Alga-derived carbon as an efficient and eco-friendly electrode material for water desalination technologies.